PENGARUH PEMBERIAN MINYAK ZAITUN DALAM PENCEGAHAN DEKUBITUS PADA PASIEN STROKE DI RUANG ICU DI MURNI TEGUH MEMORIAL HOSPITAL TAHUN 2019 - NURLELA PETRA SARAGIH (LP2MTBM MAKARIOZ, 2020)
Stroke patients are generally treated with bed rest conditions and this bed rest is an important factor causing pressure sores (pressure sores). Giving olive oil is thought to prevent pressure sores. This research type is quasy experimental research (quasy experimental). The research was conducted at Murni Teguh Hospital Medan. The population in this study were 30 people, while the sample was divided into 2 groups, namely the intervention group 15 people and the control group 15 people. Data were analyzed using t-test. The results showed that there was no difference in the degree of decubitus before (pretest) and after being given olive oil (posttest), the t-count value (-1.146) <t-table (1.761) and the significant value (0.271> 0.05). There was a significant difference in the degree of decubitus at the initial measurement (pretest) and at the final measurement (posttest), the t-count value (28.386)> t-table (1.761) and the significant value (0.000 <0.05). There were differences in the degree of pressure sores in the intervention group (given olive oil) compared with the degree of pressure sores in the control group at Murni Teguh Memorial Hospital Medan, the t-count value (23.827)> t-table (1.701) and the significant value (0.000 <0, 05).